Regionalismo latino-americano: Produção de saber e criação e importação de teoria (2023)
This paper explores the existence of Latin American voices and ideas on regional integration and evaluates if those voices have contributed to the theorizing of regionalism/regional integration. Similarly, the paper aims to contribute to the discussion on the exportability of regional integration theories, in particular, if the theoretical tools developed in the study of regional integration in Europe are of any relevance to explain and understand the processes that have taken place in Latin America and the Caribbean or even beyond it. © 2018 All rights reserved.